The Dialectic of Symbol and Image in Art - Buraq Ali Ahmed Alawadi (International Consortium of Education and Culture Research Studies, 2025)
General Background: Symbols and images have long served as fundamental components of artistic expression and visual communication across historical periods. Specific Background: The relationship between symbol and image has evolved from early artistic practices to contemporary visual culture, shaping aesthetic perception, psychological response, and cultural understanding. Knowledge Gap: Despite the widespread use of symbolism and imagery in art, the dialectical interaction between these elements and their contribution to visual culture and aesthetic experience remains insufficiently articulated across different artistic movements. Aims: This study investigates the dialectical relationship between symbol and image in art and examines how artistic imagery contributes to aesthetic perception, cognition, and cultural interpretation through selected works of Diego Velázquez, Pablo Picasso, and James Rosenquist. Results: The findings reveal that artistic images function beyond visual imitation by operating as cognitive and emotional systems that stimulate imagination, strengthen aesthetic appreciation, support memory formation, activate creative thinking, and reconstruct reality. The analyses further demonstrate that symbolic and visual elements engage both the intellect and emotions of viewers while communicating social, cultural, and political meanings. Novelty: The study presents a comparative dialectical reading of symbol and image across Renaissance, Cubist, and Pop Art contexts, highlighting their interconnected role in constructing visual culture. Implications: Understanding the interaction between symbol and image provides deeper insight into artistic communication, visual literacy, aesthetic engagement, and the cultural significance of contemporary and historical artworks. Highlights: • Demonstrates the integration of symbolic representation and visual imagery in artistic communication across multiple art movements.• Shows that artistic representations operate as cognitive and emotional systems that stimulate imagination, memory, and creative thinking.• Reveals how visual artworks communicate cultural, social, and political meanings while shaping aesthetic appreciation. Keywords: Symbolism; Visual Image; Aesthetic Perception; Visual Culture; Contemporary Art